Creation of an Indicators Model for the Evaluation of Maintenance Management in The Coffee Park - Sánchez B., Maria Angélica; Quintero Beltrán, Lewis Charles (Universidad Pontificia Bolivariana, 2020)
In this article, a model of indicators is shown to evaluate the management of maintenance of the attractions of the Coffee Park, at the present time. To do this, we recommend that you apply the RCM (Reliability Centered Maintenance) methodology to determine the causes that lead to asset failures, the level of criticism and the indicators that support preventive, corrective and predictive maintenance. Subsequently, maintenance management is assigned to the management of these assets with their own indicators and maintenance activities. Finally, a plan is obtained associated with indicators that measure the improvement of the maintenance plan against the prolongation of the life cycle of the assets and compliance with international standards that require an amusement park.